The future of evangelical theology : soundings from the Asian American diaspora - Yong, Amos (Downers Grove, Illinois : IVP Academic, an imprint of InterVarsity Press, 2014)
"Drawing on the day of Pentecost narrative, Amos Young puts forward a bold proposal for a pentecostal-evangelical theology informed by the particular experiences and perspectives of Asian Americans. The Future of Evangelical Theology is a personal and programmatic vision for theology that pays attention to the realities of gender, race, migration, economics, justice and politics. What emerges is a theology situated within a Pentecostal Asian American context that bears on the future of the whole church. -- Back Cover.
Evangelicalism and global theology : emerging Asian and contextual voices -- Asian American Christianity : wider trends and trajectories -- The legacy of evangelical theology : Asian American reception and interrogations -- Pentecostal voices : toward an Asian American evangelical theology -- The im / migrant spirit : toward an evangelical theology of migration -- The spirit of jubilee : an Asian American immigrant consideration -- Toward a global evangelical theology : Asian American intonations.
Online resource; title from PDF title page (Ebsco, viewed Jan. 15, 2015).
Includes bibliographical references and indexes.
Master record variable field(s) change: 050
Keywords: Evangelicalism -- Forecasting; Pentecostalism; Asian Americans -- Religious life; Christianity -- Asia; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Asian Americans -- Religious life; Christianity; Evangelicalism -- Forecasting; Pentecostalism; Asia; Electronic books; Electronic books